2004
DOI: 10.1097/01.gim.0000127267.57526.d1
|View full text |Cite
|
Sign up to set email alerts
|

Molecular screening for diseases frequent in Ashkenazi Jews: Lessons learned from more than 100,000 tests performed in a commercial laboratory

Abstract: Purpose: To determine the frequency of carriers of Ashkenazi Jewish (AJ) genetic diseases in the US population and compare these numbers with previously published frequencies reported in smaller more isolated cohorts. Methods: A database containing more than 100,000 genotyping assays was queried. Assays for 10 separate AJ genetic diseases where comparisons were made with published data. Results: As expected, we observed lower carrier frequencies in a general, US population than those reported in literature. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 38 publications
2
23
0
Order By: Relevance
“…The frequency of the IVS3-2AϾG is approximately three times that of the 511del6434. Previous data published by this laboratory 10 reported a carrier frequency of 1:182, although the number of samples was lower (n ϭ 2006). The larger number of samples tested in the current study yielded a carrier frequency more consistent with other reports (Table 2).…”
Section: Platform Comparisonmentioning
confidence: 86%
See 1 more Smart Citation
“…The frequency of the IVS3-2AϾG is approximately three times that of the 511del6434. Previous data published by this laboratory 10 reported a carrier frequency of 1:182, although the number of samples was lower (n ϭ 2006). The larger number of samples tested in the current study yielded a carrier frequency more consistent with other reports (Table 2).…”
Section: Platform Comparisonmentioning
confidence: 86%
“…The results for 2006 of these cases were published previously. 10 Seventy-seven chromosomes of 21,054 carried the IVS3-2AϾG mutation for a mutant allele frequency of 0.37% while 25 chromosomes carried the 511del6434 mutation for an allele frequency of 0.12%. The heterozygote carrier frequency was 0.73% for the IVS3-2AϾG and 0.24% for the 511del6434; the combined carrier frequency was 0.97% or 1:103 individuals and a predicted disease incidence of ϳ1:42,436.…”
Section: Allele Frequency In Our Tested Populationsmentioning
confidence: 99%
“…In unaffected mutation carriers of autosomal recessive conditions, one or more heterozygous mutations are expected in the entire array, as long as the heterozygous mutations are not present in compound heterozygous form in the same gene. Strom and colleagues 14 reported that in a limited panel of eight AJ disorders, approximately one in seven individuals is a carrier of at least one heterozygous mutation. Affected patients are expected to carry two mutations, either two different mutations in the same gene or a homozygous mutation.…”
Section: Resultsmentioning
confidence: 99%
“…One of these (LDT1) tested for BS, CD, FA, FD, GD, MLIV, NP, TSD, and GSD using previously described methods (Table 3). 10 This laboratory assayed for BS, FA, and FD mutations using the Promega ReadIT SNP Genotyping System (Promega Incorporated, Madison, WI). MLIV mutations were assayed using real-time PCR on an ABI7900 (Applied Biosystems, Foster City CA), and CD, GD, NP, TSD, and GSD assays were preformed using SnapShot kits (Applied Biosystems Incorporated, Foster City, CA).…”
Section: Assay Methodsmentioning
confidence: 99%